The Mediating Role of Purchase Intention on the Effect of Product Quality and Price Fairness on Purchasing Decisions - Kadek Geby Oktaviari; Agus Wahyudi Salasa Gama; I Gusti Agung Eka Teja Kusuma (Universitas Pendidikan Ganesha, 2023)
Children's apparel sector is surging in Indonesia, posing challenges for children's clothing retailers, exemplified by CV. Patras Development. In the realm of heightened market competition, innovation becomes imperative. CV. Patras Development grapples with obstacles such as external competitors offering more cost-effective solutions and raw material sourcing intricacies, compounded by a tranquil business environment in Bali. This quantitative research adopts a methodological approach focusing on latent variables—Product Quality (X1) and Price Fairness (X2) as influencers, and Purchase Interest (Y1) and Purchasing Decisions (Y2) as influenced variables. The study encompasses 72 consumers of children's clothing at CV. Patras Development, with data meticulously processed using SmartPLS accounting software. The findings elucidate that Product Quality and Price Fairness significantly influence the purchasing interest of clothing consumers at CV. Patras Development. Noteworthy is the positive impact of Price Fairness on purchasing decisions, whereas Product Quality and Purchase Intention exhibit no discernible effect on purchasing decisions. Intriguingly, the mediation of Purchase Intention between product quality and price fairness proves inconsequential in shaping purchasing decisions among clothing consumers at CV. Patras Development from an accounting perspective.